Status of Battery in Indonesia to Support Application of Solar PV with Energy Storage - Dwipayana, I Putu Gede Iwan; Kumara, I Nyoman Satya; Setiawan, I Nyoman (Journal of Electrical, Electronics and Informatics, 2021)
Indonesia plans to build solar PV plants to reach 6500 MW capacity by 2025. One of the solar PV applications is systems with battery storage systems. In this system, the battery is an important component of the solar PV system as it stores the energy for use when the sun is unavailable. This article reviews the status of batteries in Indonesia to support the proliferation of solar PV applications. The objective is to compile a battery database for solar PV applications. The database provides insight into technology and the availability of batteries. The database consists of 361 batteries of various technologies such as FLA, VRLA, VRLA gel, VRLA AGM, and Lithium-ion. The most widely available is the VRLA gel. In terms of voltage, batteries are available at 2 to 12 volts and with capacity from 1 to 3000 Ah. The availability of batteries shows that this field is ready to support the development of solar PV with energy storage although the field of battery recycling or its waste management requires more attention.